Exploring Determining Factors: Revisitation Intention Influenced by Environmental Knowledge, Accessibility Quality, Attractiveness, and Social Media - Arifin, Samsul; Eka, Mochamad Dimas; Arifiana, Ana; Fitaloka, Ersa Dina; Fitri, Rohmadhotin; Sinambela, Ella Anastasya; Halizah, Siti Nur; Lestari, Utami Puji (Sustainable Environmental and Optimizing Industry Journal, 2023)
This study aims to investigate the effect of environmental knowledge, quality of accessibility, attractiveness, and social media on the intention to return to an Eco Green Park tourist destination. The type of data used is primary data which is quantitative in nature. Primary data was obtained from distributing questionnaires to tourists visiting Eco Green Park. Respondents amounted to 100 people. The collected data were analyzed using statistical methods such as multiple linear regression. The results showed that environmental knowledge and accessibility quality had a significant effect on the intention to return. Understanding of the environment and good accessibility experiences can influence tourists' perceptions of destinations. For the next result, attractiveness has a significant effect on the intention to visit again. The last shows significant results between social media and intention to revisit, because information and reviews spread on social media platforms can influence tourist perceptions and decisions.